Liquid application dosing alters the physiology of air-liquid interface (ALI) primary human bronchial epithelial cell/lung fibroblast co-cultures and in vitro testing relevant endpoints - Mallek, Nicholas M.; Martin, Elizabeth M.; Dailey, Lisa A.; McCullough, Shaun D. (Frontiers in Toxicology, 2024)
Differentiated primary human bronchial epithelial cell (dpHBEC) cultures grown under air-liquid interface (ALI) conditions exhibit key features of the human respiratory tract and are thus critical for respiratory research as well as efficacy and toxicity testing of inhaled substances (e.g., consumer products, industrial chemicals, and pharmaceuticals). Many inhalable substances (e.g., particles, aerosols, hydrophobic substances, reactive substances) have physiochemical properties that challenge their evaluation under ALI conditions in vitro. Evaluation of the effects of these methodologically challenging chemicals (MCCs) in vitro is typically conducted by “liquid application,” involving the direct application of a solution containing the test substance to the apical, air-exposed surface of dpHBEC-ALI cultures. We report that the application of liquid to the apical surface of a dpHBEC-ALI co-culture model results in significant reprogramming of the dpHBEC transcriptome and biological pathway activity, alternative regulation of cellular signaling pathways, increased secretion of pro-inflammatory cytokines and growth factors, and decreased epithelial barrier integrity. Given the prevalence of liquid application in the delivery of test substances to ALI systems, understanding its effects provides critical infrastructure for the use of in vitro systems in respiratory research as well as in the safety and efficacy testing of inhalable substances.